Employee-Organization Congruence and Job Performance: Development of a Conceptual Model - Perera, G.D.N. (i-Proclaim, 2013)
Research on Employee-Organization Congruence (EOC) has focused on the effect of EOC on individual performances. However EOC and job performance relationship and its contextual validity have not been explored in Sri Lankan apparel sector. This paper has explored the specific factors specially related to the Sri Lankan apparel sector work environment. Among these variables EOC considered as independent variable, job performance as a dependent variable. The conceptual model of this study investigates job related attitudes, namely job satisfaction and organizational commitment as two potential mediating factors for the  EOC and job performance relationship. Further organizational climate has been cited as possible moderating factor on EOC and job performance relationship. This paper makes a significant contribution to the body of knowledge with the proposed conceptual framework so that it can be used as a basis for the future research in this context. JEL Classification Code: J53; J58